Properties of Solutions to Stochastic Set Differential Equations under Non-Lipschitzian Coefficients - Weiyin Fei; Yunhe Li; Chen Fei (Abstract and Applied Analysis)
A class of stochastic set differential equations (SSDEs) with non-Lipschitzian coefficients is investigated. We first give the preliminaries on the stochastic set differential equations. Then the nonexplosion of solutions to the SSDEs is discussed. Moreover, the existence and uniqueness of the solutions to SSDEs are proven. Finally, the continuous dependence of the solutions to SSDEs is studied.